The Success of the Link Model Programme in Rural Bangladesh: An Empirical Analysis. (July 2018) - Takeda, Shutaro; Okui, Go; Fujimura, Nanao; Abe, Hisae; Ohashi, Yuka; Oku, Yuki; Kiriyama, Kyoko; Saeki, Naoki; Sasaki, Yusuke; Zhu, Yingying; Shu, Keitou; Takahashi, Tomoharu; et al.
Abstract: Link Model, a participatory rural appraisal (PRA) programme for micro-infrastructure construction funding aid, has received much attention in Bangladesh over the last few decades. This study aims to contribute to the latest phase of the Link Model project, launched in July 2016 by the Bangladeshi government. To this end, the authors conducted a field survey in Kalihati Upazila, which involved 102 villagers and 153 local representatives. The authors used the survey to examine the efficacy of the programme and to identify the key factors that contribute to its success. Results obtained from the questionnaire survey showed that the programme had high degrees of satisfaction and penetration in the surveyed villages. Moreover, the degree of satisfaction was unaffected by gender, religion, income or education background, which is notably consistent with the ideals of PRA. Villagers who understood the policy better were more satisfied with the micro-infrastructures developed through the Link Model programme. The ratings of union development officers (UDO) strongly correlated with the number of micro-infrastructures. Therefore, this study concludes that the key success factors of Link Model are (a) the understanding of villagers on the programme for quality and (b) the capability of UDO for quantity.